Physical activity and mental health in Brazilian university students: An analysis in different sexes during the COVID-19 pandemic - Santos Gabriela Carvalho Jurema; Rino Mateus Jurema; da Silva Lima Victor Luiz; Santos José Adilson; da Silva Fidelis Débora Eduarda; Ramos Tiago Lacerda; de Andrade Adelmo José; de Lira Camila Tenório Calazans; de Souza Fernandes Matheus Santos (Sciendo, 2023)
Study aim: To identify symptoms of depression, anxiety, and stress in Brazilian university students of both sexes and the association of physical activity parameters during the COVID-19 pandemic.